SMEs Halal Compliance in the Implementation of Service Operations Management - Anwar, Umari Abdurrahim Abi; Nurhakim, Haditsa Qur'ani; Rani, Asni Mustika (The Eastasouth Management and Business, 2024)
Possession of halal certification does not necessarily ensure that SMEs have high halal compliance. Halal compliance is important to ensure the quality of SME products, including their service products. This study analyzes SME halal compliance in the implementation of service operations management. Descriptive and verification methods are used to test the hypothesis using regression. Some SMEs in Indonesia which are in the food and beverage processing industry sector already have halal standard criteria, although some have not yet received halal certification. Other business sectors are not yet halal certified because they still feel it is not urgent. There is an influence between halal compliance and the implementation of service operations management. The service operations management system model refers to effective, efficient and productive fundamentals, which are efforts not to deviate from other than what has been prescribed by Islam.